Role of acid-treated CNTs in chemical and electrochemical impedance study of dye-sensitised solar cell - Mahalingam S.; Abdullah H.; Manap A. (Elsevier Ltd, 2023)
Carbon; Carbon nanotubes; Chemical analysis; Chemical bonds; Defects; Efficiency; Electrochemical impedance spectroscopy; Electrons; Energy gap; Fourier transform infrared spectroscopy; High resolution transmission electron microscopy; Indium compounds; Multiwalled carbon nanotubes (MWCN); Nanotubes; Open circuit voltage; Sol-gel process; Sol-gels; Solar cells; Spectrum analysis; Thin films; X ray photoelectron spectroscopy; Yarn; Acid treatments; Body-centered-cubic phase; Electrical; Electrochemical impedance; Electron recombinations; Internal structure; Visible spectrophotometries; X ray diffractometers; Dye-sensitized solar cells